Steroidal Saponins from the Rhizomes of Anemarrhena asphodeloides - Yang, Bing-You (Molecules, 2016)
Four new steroid saponins 1–4 were isolated from the rhizomes of Anemarrhena asphodeloides (Asparagaceae), as well as four known saponins: anemarsaponin B (5) timosaponin D (6), timosaponin E1 (7) anemarsaponin B II (8). Their structures were established through UV and NMR as well as MS data. All the compounds were evaluated for cytotoxicity against HepG2 and SGC7901 human cancer lines. Compounds 3 and 7 displayed medium antiproliferative activities on HepG2 and SGC7901 cells, with IC(50) values of 43.90 and 57.90 μM, respectively.